An investigation of myosin binding protein C mutations in South Africa and a search for ligands binding to myosin binding protein C - De Lange, W. J. (Willem Jacobus) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD)--University of Stellenbosch, 2004.